The impact of material and crafting technology on the shaping and design of wrought iron architectural elements - Vidovszky, István (Journal of Architecture and Urbanism, 2023)
Wrought iron was a determining material in historic times. Although it was mainly used for manufacturing tools and weapons it was also applied for architectural purposes as building structural or architectural elements. In this paper the impact of material and technology of forging on the shaping and the design of wrought iron building structural and architectural elements from the time of the first known application to the 20th century in Europe is analyzed, distinguishing five main periods which are divided by four determining technological shifts in material production and consequently forging technology. Several phenomena are delighted regarding the appearance of the artifacts and the characteristics of the material, which reveal connections between technology and architectural design. The observations are validated by visual analyses of wrought iron samples.